2009
DOI: 10.1007/978-3-642-02818-2_17
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Use of Web-COBRA and Web Objects to Estimate Web Application Development Effort

Abstract: Abstract.We have performed a replication of a previous study in order to further assess the effectiveness of Web-COBRA method, with the Web Objects measure, in predicting Web application development effort. The results of the empirical analysis confirm the interesting results of the previous study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results revealed that the Web Objects measure is a good indicator of the development effort since we obtained MMRE=0.14, MdMRE=0.06, and Pred(25)=0.75. Moreover, in [12] we assessed the use of Web Objects in combination with Web-COBRA, using only dataset I of Table 1, with a leave-1-out cross validation, obtaining MMRE=0.11, MdMRE=0.10, and Pred(25)=0.93.…”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…The results revealed that the Web Objects measure is a good indicator of the development effort since we obtained MMRE=0.14, MdMRE=0.06, and Pred(25)=0.75. Moreover, in [12] we assessed the use of Web Objects in combination with Web-COBRA, using only dataset I of Table 1, with a leave-1-out cross validation, obtaining MMRE=0.11, MdMRE=0.10, and Pred(25)=0.93.…”
Section: Discussion and Comparisonmentioning
confidence: 99%